Okra (Abelmoschusesculentus L. Moench) pectin: extraction yield and chemical composition - Abd Rahman, Nur Farhana; Al-Sheraji, Sadeq Hassan; Ismail, Amin; Mustafa, Shuhaimi (Halal Products Research Institute, Universiti Putra Malaysia, 2014)
Pectin was extracted from okra (Abelmoschusesculentus(L.) Moench) leaves, pulp (fruit without seeds) and seeds using a sequential extraction with the applications of hot buffer (HB), hot buffer with chelating agents (CH), diluted alkali (DA) and concentrated alkali (CA) soluble solids. The fractions obtained from these extraction methods were compared with commercial pectin in order to identify their chemical compositions and functional groups using Fourier Transform Infrared Spectroscopy (FTIR). CH extraction gave the highest pectin yield (>40%) compared to HB and DA. The HB fraction harbored highly purified pectin due to high anhydrouronic acid content and degree of esterification. The highest pectin yield was extracted from seeds with an overall fraction yield of 86%, followed by the leaves (75%) and pulp (71%). Okra seeds were found to display the highest yield compared to okra leaves and pulp. The HB fractions display the highest possibility of representing a great source of pectin, as its chemical composition matches commercial pectin the best.